Development and Validation of a Microbiological Agar Assay for Determination of Orbifloxacin in Pharmaceutical Preparations - Hérida R. N. Salgado; Edith C. L. Cazedey (MDPI AG, 2011)
Orbifloxacin is a fluoroquinolone with broad-spectrum antimicrobial activity, and belongs to the third generation of quinolones. Regarding the quality control of medicines, a validated microbiological assay for determination of orbifloxacin in pharmaceutical formulations has not as yet been reported. For this purpose, this paper reports the development and validation of a simple, sensitive, accurate and reproducible agar diffusion method to quantify orbifloxacin in tablet formulations. The assay is based on the inhibitory effect of orbifloxacin upon the strain of Staphylococcus aureus ATCC 25923 used as test microorganism. The results were treated statistically by analysis of variance and were found to be linear (r = 0.9992) in the selected range of 16.0-64.0 μg/mL, precise with relative standard deviation (RSD) of repeatability intraday = 2.88%, intermediate precision RSD = 3.33%, and accurate (100.31%). The results demonstrated the validity of the proposed bioassay, which allows reliable orbifloxacin quantitation in pharmaceutical samples and therefore can be used as a useful alternative methodology for the routine quality control of this medicine.